Study of transport and exitonic related optical phenomenain lowdimensional semiconductor structures. (2004)
In this project it is proposed to study the transport phenomena with in-plane applied magnetic fields in double barrier semiconductor heterostructures as well as the role of the channels offered by impurity states provided by well-on-center located impurities in this kind of structures Also we will study excited excitonic states in low dimensional semiconductor heterostructures, such as in quantum well-wires, quantum dots and in single and coupled double quantum wells. Special attention will be devoted to the study of the dependence of the excitonic binding energy with the size of the structure, with the interaction with doping impurities, with applied electric and magnetic fields. The calculation of the optical response due to excitonic states will be carefully studied. For the study of the transport properties in low-dimensional semiconductors we will employ the Green function technique developed by Keldysh for non-equilibrium systems. For the study of excited excitonic states in low dimensional semiconductor heterostructures we will use the effective mass approximation within the variational scheme and alternatively we will use the fractional dimension approach. We will compare our results with recent theoretical and experimental reports.